Heroes of the smile: An experience of oral health promotion in children of a Non-Governmental Organization (NGO) (Research, Society and Development, 2023)
The Heroes of Smiles Program: "Humanizing glances for a rescue of attitudes" is an extension project of the Federal University of Campina Grande (UFCG) made up of 3 axes. The NGO axis carries out activities at the Operação Resgate institution and provides general health promotion and oral health guidance to the children who attend. The aim of this study is to report on the experience of the NGO Operação Resgate - Patos/PB of the Heróis do Sorriso (Heroes of Smiles) program during 2019. This is a descriptive qualitative study of the experience report type. The actions were carried out weekly from May to December 2019 at the NGO itself, with just over 150 children divided into age groups. The activities covered various important topics such as caries, diet and dental trauma, which were taught in a playful way to arouse interest and facilitate the children's learning process. Through its creative methodology, the program managed to create a strong bond of trust with the children, facilitating clinical care for those who were in an intervention situation and were referred to the UFCG school clinic, achieving success and helping to improve their quality of life, thus fulfilling an important partnership role with the NGO. For the students, the benefits are innumerable: in addition to their technical knowledge, they come out of this experience more humanized, often receiving more than they give.